(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study determined the level of competence of Zamboanga Peninsula Polytechnic State University students in the use of technologies for flexible learning in the new normal in terms of; a) learning management system; (b) digital tool application and; (c) virtual meeting application. The study employed mixed methods of qualitative and quantitative approaches in determining the said competencies. One-hundred-twenty (120) respondents were chosen from Zamboanga Peninsula Polytechnic State University’s three colleges. The results revealed that all components in the learning management system yielded the intermediate level of competencies; Google Classroom was rated advanced level, Canvas, Edmodo, and Moodle were intermediate. In digital tool application yielded the intermediate level of competencies in which Kahoot and Quizizz were rated as intermediate while Google Suites as advanced. While in Virtual Meeting Application yielded an advanced level of competencies; Zoom and Google Meet respectively were rated as the advanced level of competency. In addition also about determining the difference of the three level of competence among the respondence ated, it was found out that there is no significant difference in the level of competence in the use of technology applications such as Learning Management System (LMS), Digital Tool Application (DTA), and Virtual Meeting Application (VMA).